Near-field elastomeric mask photolithography fabrication of high-frequency surface acoustic wave transducers - Hesjedal, T; Seidel, W (2003)
Optical lithography is the method of choice for mass production of electronic as well as acoustic devices. Cost issues, in particular, make it superior over slow but high-resolution methods, such as electron beam lithography. Also, its applicability for nonconductive substrates is an important feature for acoustic device fabrication on ceramics. In order to be able to continue the use of diffraction-limited optical lithography, new schemes have been developed that enhance the resolution. Rather complex phase-shifting masks, for instance, alter both the amplitude and the phase of the exposing light and lead to higher resolution. However, by using an elastomeric phase mask derived from a photoresist master (made by conventional photolithography), features as small as 90 nm have been demonstrated. We report on the application of the near-field phase shift technique for the fabrication of surface acoustic wave (SAW) devices. This technique is best suited for the fabrication of narrow electrode gap SAW devices that are designed for the efficient SAW excitation at higher harmonics. The combination of near-field phase shift lithography with narrow-gap SAW designs thus opens up a way for simple and low-cost SAW devices operating above 5 GHz.